2012
DOI: 10.1111/j.1754-9434.2012.01419.x
|View full text |Cite
|
Sign up to set email alerts
|

Intelligence 2.0: Reestablishing a Research Program on g in I–O Psychology

Abstract: Intelligence (i.e., g, general mental ability) is an individual difference that is arguably more important than ever for success in the constantly changing, ever more complex world of business (Boal, 2004; Gatewood, Field, & Barrick, 2011). Although the field of industrial–organizational (I–O) psychology initially made substantial contributions to the study of intelligence and its use in applied settings (e.g., Hunter, 1980; Schmidt & Hunter, 1981), we have done relatively little in recent times about studying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 79 publications
(161 reference statements)
3
46
0
1
Order By: Relevance
“…Our main point, and one that has been noted elsewhere (e.g., Lievens & Reeve, 2012;Reeve & Charles, 2008;Scherbaum et al, 2012), is that the treatment of "intelligence" in HR and I-O psychology lags far behind the science of mental abilities. Thus, it is not a surprise that many of the measures that have been developed to capture the manifestations of the complex skills and competencies required for success in today's workplace are not based on the science and theory of mental abilities.…”
Section: What Is "Intelligence"? a Brief Updatementioning
confidence: 96%
See 3 more Smart Citations
“…Our main point, and one that has been noted elsewhere (e.g., Lievens & Reeve, 2012;Reeve & Charles, 2008;Scherbaum et al, 2012), is that the treatment of "intelligence" in HR and I-O psychology lags far behind the science of mental abilities. Thus, it is not a surprise that many of the measures that have been developed to capture the manifestations of the complex skills and competencies required for success in today's workplace are not based on the science and theory of mental abilities.…”
Section: What Is "Intelligence"? a Brief Updatementioning
confidence: 96%
“…A second challenge is that the field has lost contact with differential psychology and measurement theory (e.g., Schmidt, 2002;Schmidt & Hunter, 1998;Scherbaum et al, 2012). Overall, graduate training across North America systematically decreased the amount of training in differential psychology, measurement and psychometrics (Aiken et al, 1990).…”
Section: Challenges Of Using Intellectual Competencies As Construct Cmentioning
confidence: 97%
See 2 more Smart Citations
“…In relation to the first, Scherbaum, Goldstein, Yusko, Ryan, and Hanges (2012) argue that traditional conceptualizations of intelligence remain overvalued and that new conceptualizations are under-researched in the organizational psychology and training literature (though see, Ackerman, 1996, for an earlier comment on this). Sitzmann and Ely's (2011) more recent meta-analysis of self-regulated learning in work-related training confirmed that taken together, self-regulatory variables provide significant incremental prediction and largely debunk the ubiquitous status of cognitive abilities as the predictor of learning outcomes (17% of the variance in learning was accounted for by goals, persistence, effort, and self-efficacy, after controlling for cognitive ability).…”
Section: Introductionmentioning
confidence: 98%